Exchange Rate Pass-through in Russia - Yuri Ponomarev; Pavel V. Trunin; Aleksej V. Uljukaev (Gajdar Institute for Economic Policy, 2014)
The article provides estimates of short-run and medium-run exchange rate pass-through into domestic prices in Russia during the period of 2000–2012 using vector error correction model. Exchange rate pass-through asymmetry estimates, its assessments on different sub-periods and exchange rate volatility effect on pass-through are also provided. – – 2000-2012 . , - .
Keywords: C32; E31; E52; F31; F41; 330; exchange rate pass-through; asymmetry of exchange rate pass-through; exchange rate volatility; inflation; monetary policy; vector error correction model